The Effect of Promotion and Service Factors on Airplane Transportation Ticket Prices on the Traveloka E-commerce Application - Ashari, Rizka Reyka; Dewi, Tania Kartika; Ananda, Rezky Amalia; Nusa, Yahya (ProBisnis : Jurnal Manajemen, 2024)
In the Traveloka e-commerce application, airplane transportation ticket prices often change greatly, which makes customers confused and dissatisfied. The purpose of this study is to find and analyze the main factors that cause unstable airfares at Traveloka. Descriptive and qualitative analysis were used to analyze this data. In addition, multiple regression analysis was conducted using the SPSS 25 computer program. The results of this study are expected to be a motivation for Traveloka to implement a more fair and open pricing system, not raising prices too high and significantly because customers also want prices that match the facilities they receive. In addition, it is hoped that the results of this study can encourage further research on pricing practices in the digital era. This will help make better policies and regulations to protect consumers in the digital era.